Flow Path of the Carbonate Geothermal Water in Xiong’an New Area, North China: Constraints From 14C Dating and H-O Isotopes - Zhang, Baojian; Wang, Siqi; Kang, Fengxin; Li, Yanyan; Zhuo, Linyang; Gao, Jun; Yuan, Wenzhen; Xing, Yifei (Frontiers in Earth Science, 2022)
Studying the flow path of geothermal water in geothermal fields is an important basis for the scientific development and management of geothermal resources. However, due to the influence of engineering volume, economic benefits and demand, it is very difficult to fully grasp the flow path of deep geothermal water in large areas. The use of hydrogeochemical tracers to determine the flow path of geothermal water is a scientific and effective research method. In order to accurately describe the flow path of carbonate geothermal water in the Xiong’an New Area and its surrounding areas, this study systematically analyzed the 14C, 18O, and 2H data of carbonate and Cenozoic sandstone geothermal water, Quaternary groundwater, as well as mountain spring water of the study area. Based on these results, we can conclude that 1) The 14C, d, and 18O values are favourable clues for indicating the circulating runoff conditions and runoff paths of geothermal water. 2) The salinity of the Xushui-Wenan and Lilan transfer zone are <3 g/l, the 14C values are lower than 25000 years, the d value is higher, and the phenomenon of “18O drift” is weak, all these indicating the dominant flow path of carbonate geothermal water, featured by relative lower temperature. 3) The salinity of karst geothermal water in the southwest of Gaoyang low uplift, Rongcheng uplift and Niutuozhen uplift is > 3 g/l, the 14C values are higher than 40,000 years, the d value is lower, and the phenomenon of “18O drift” is obvious, all these indicating that the tectonic sites are the convergence areas of regional karst geothermal water, featured by relative high temperature. 4) The hydrochemical indicators combined with previous carbonate groundwater flow field indicate that the recharge of carbonate geothermal water in the Xiong’an New Area may not only drive from the western Taihang Mountains, but also along the Xushui-Wenan transfer zone and the Lilan fault, with the recharge of carbonate groundwater from the Cangxian uplift from east to west. By further identifying and defining the dominant flow path and supply direction of carbonate geothermal water in the Xiong’an New Area and surrounding areas, it provides strong support for the scientific development of regional carbonate geothermal water.